Cellular heterogeneity in granulosa cells of developing goat follicles - SANGHA, G K; MARWAHA, A; KAUR, TEJINDER; BILASPURI, G S (The Indian Journal of Animal Sciences, 2014)
The histomorphology and histochemistry of the granulosa cells from small (5mm) follicles of goat ovaries was studied. The granulosa cells present in the antral follicles are distinguished into mural, middle, antral, cumulus and corona-radiata cells. Histomorphologically the granulosa cells from different layers of developing follicles differ in cell shape and size. Histochemically, mllcopolysaccharides stain differentially with periodic acid Schiff reagent (PAS) and alcian blue (pH 2.5) in granulosa cells of different layers of growing follicles. The results suggested that the granulosa cells undergo morphological and functional changes in developing follicles.